A game-theoretical model for inter-organisational collaboration in information systems development. (1st January 2011) - Chou, P. Ben
This paper develops a game-theoretical model to address different levels of cooperation between two firms that share their knowledge/information systems as a local public good. The model shows that the collaboration between two firms can lead to the creation of new knowledge/information technology, and that a higher speed of creating new knowledge can change the structure of the game from a prisoners' dilemma game to a coordination game as an evolutionary process. Therefore, despite the knowledge-sharing dilemma, it is possible for both firms to reach the stable and more efficient full-collaboration equilibrium than the Nash collaboration equilibrium.